Expression and production of the SERPING1-encoded endogenous complement regulator C1-inhibitor in multiple cohorts of tuberculosis patients. (April 2020) - Lubbers, Rosalie; Sutherland, Jayne S.; Goletti, Delia; de Paus, Roelof A.; Dijkstra, Douwe J.; van Moorsel, Coline H.M.; Veltkamp, Marcel; Vestjens, Stefan M.T.; Bos, Willem J.W.; Petrone, Linda; Malherbe, Stephanus T.; Walzl, Gerhard; et al.
Highlights: SERPING1 expression was increased in patients with active tuberculosis. C1-inhibitor proteins levels were increased in half of the TB cohorts analysed. C1-inhibitor was not increased in other clinically relevant conditions. C1-inhibitor levels normalised over the course of treatment. A positive correlation between C1q and C1-inhibitor was found in TB patients. Abstract: Background: To facilitate better discrimination between patients with active tuberculosis (TB) and latent TB infection (LTBI), whole blood transcriptomic studies have been performed to identify novel candidate host biomarkers. SERPING1, which encodes C1-inhibitor (C1-INH), the natural inhibitor of the C1-complex has emerged as candidate biomarker. Here we collated and analysed SERPING1 expression data and subsequently determined C1-INH protein levels in four cohorts of patients with TB. Methods: SERPING1 expression data were extracted from online deposited datasets. C1-INH protein levels were determined by ELISA in sera from individuals with active TB, LTBI as well as other disease controls in geographically diverse cohorts. Findings: SERPING1 expression was increased in patients with active TB compared to healthy controls (8/11 cohorts), LTBI (13/14 cohorts) and patients with other (non-TB) lung-diseases (7/7 cohorts). Serum levels of C1-INH were significantly increased in The Gambia and Italy in patients with active TB relative to the endemic controls but not in South Africa or Korea. In the largest cohort (n = 50), with samples collected longitudinally, normalization of C1-INH levels following successful TB treatment was observed. This cohort, also showed the most abundant increase in C1-INH, and a positive correlation between C1q and C1-INH levels. Combined presence of increased levels of both C1q and C1-INH had high specificity for active TB (96 %) but only very modest sensitivity 38 % compared to the endemic controls. Interpretation: SERPING1 transcript expression is increased in TB patients, while serum protein levels of C1-INH were increased in half of the cohorts analysed.